Karakteritik Ekstrak Kulit Buah Kakao Sebagai Pewarna Alami Pada Variasi Jenis Pelarut dan Daya Ekstraksi Dengan Metode Microwave Assisted Extraction - Agustina, Dwy Ristika Sari; Putra, Gusti Putu Ganda; Hartiati, Amna (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Cocoa pods contain flavonoid compounds that can be used as natural colourants. These compounds can be obtained through an extraction process, one of which uses the Microwave Assisted Extraction method. This study was conducted to determine the effect of solvent type and power on extraction using the Microwave Assisted Extraction method on the characteristics of cocoa fruit skin extract and to determine the best combination of solvent type and power to produce cocoa fruit skin extract as a natural colourant. The experimental design used was factorial randomized block design with 2 factors grouped based on the time of implementation. The first factor is the type of solvent consisting of 3 type, namely ethanol, methanol, and acetone. The second factor is extraction power consisting of 3 levels, namely 300, 450, and 600 watts. The data were analyzed by analysis of variance and continued with Tukey test. The results showed that the type of solvent and extraction power and their interaction had a very significant effect on yield, total flavonoids, L*a*b* color intensity, but the treatment of solvent type and power and their interaction did not significantly affect the colour scoring and liking of cocoa pod skin extract. From the effectiveness index test, the best treatment to obtain cocoa pod skin extract as a natural dye was ethanol solvent and 600 watts power, with characteristics of yield 4.56 ± 0.27%, total flavonoids 9.48 ± 0.30 mg QE/g, L* 37.55 ± 1.34, a* 26.55 ± 0.92, b* 58.6 ± 1.70, colour scoring 4.55 ± 0.60 (less bright brown - not bright brown), and liking 4.25 ± 0.64 (neutral - somewhat like).